2013
DOI: 10.1007/s00330-013-3060-2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic outlet syndrome in 3T MR neurography—fibrous bands causing discernible lesions of the lower brachial plexus

Abstract: • MR neurography (MRN) can aid the diagnosis of thoracic outlet syndrome (TOS). • Identifiable causes of TOS in MRN include fibrous bands and bony anomalies. • Increased T2W signal within brachial plexus elements indicate relevant nerve compression. • High positive predictive value allows confident and targeted indication for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 14 publications
1
48
0
7
Order By: Relevance
“…18 Diagnostic accuracy of MRN has been widely reported in literature. 8,[19][20][21] However, studies demonstrating the impact on clinical management and patient outcomes are limited. Andreisek et al 22 found moderate to major impact in the evaluation of the majority of upper extremity neuropathies (84%) with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…18 Diagnostic accuracy of MRN has been widely reported in literature. 8,[19][20][21] However, studies demonstrating the impact on clinical management and patient outcomes are limited. Andreisek et al 22 found moderate to major impact in the evaluation of the majority of upper extremity neuropathies (84%) with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…По данным ряда авторов, посттравматические причины составля-ют до 2 / 3 случаев TOS [23,24]. К развитию TOS могут привести переломы ключицы, однократные или по-вторные травмы плеча, повреждения шейного отдела позвоночника.…”
Section: том 7 Volunclassified
“…В России рутинная МР-визуализация нервных стволов в целях диагности-ки и дифференциальной диагностики по-прежнему используется недостаточно. Однако правильная поста-новка задачи и методически адекватно проведенное МР-исследование могут значительно помочь клини-цисту, особенно при отсутствии электрофизиологиче-ских изменений [23,46,47]. Информативность МРТ в диагностике TOS возрастает при ее выполнении с позиционными пробами и провокационными теста-ми [47][48][49].…”
Section: инструментальная диагностикаunclassified
“…Initial studies suggest that these highquality images play an important role in confirming the diagnosis of nTOS. 2 MRN can be performed using a number of variations on several fundamental techniques. Commonly obtained sequences include standard spin-echo T1-and fast spinecho T2-weighted images with fat suppression.…”
Section: Advances In Mr Neurography and Tractographymentioning
confidence: 99%